Accidents caused by venomous animals: An important public health problem in a municipality in the state of Pará in the Brazilian Amazon (Research, Society and Development, 2024)
Accidents caused by venomous animals are considered by the World Health Organization (WHO) as neglected tropical diseases. The present study aimed to analyze the occurrence of accidents caused by venomous animals in the municipality of Brazil Novo in the state of Pará, in the Brazilian Amazon, from 2019 to 2022. This is a descriptive and retrospective epidemiological analysis of the cases of accidents caused by venomous animals recorded from January 2019 to July 2022, in the municipality of Brazil Novo. Data from the Notifiable Diseases Information System (SINAN) reported 686 cases of accidents caused by venomous animals. Most of the accidents occurred in rural areas (71.57%), in male patients (69.39%), adults aged 20 to 59 years (64.72%), mainly with scorpions (71%) and snakes (12.53%). Serum therapy was used in 20.55% of the accidents and was not necessary in 79.45% and the year 2019 stood out with more occurrences (31.78%). Even with a decline in the numbers reported and no deaths, the municipality of Brazil Novo continues to register a significant number of accidents caused by venomous animals, which in turn has been causing concern for public health, making it essential to maintain studies and actions that encourage the local population to become aware of prevention and control measures, in order to prevent new accidents. Serum therapy is a form of control, a resource that protects the population, but generates costs for local public health.